HPV16 genome structure analysis in oropharyngeal cancer PDXs identifies tumors with integrated and episomal genomes - Claire D. James; Raymonde O. Otoa; Aya H. Youssef; Christian T. Fontan; Malay K. Sannigrahi; Brad Windle; Devraj Basu; Iain M. Morgan (Tumour Virus Research)
HPV + oropharyngeal squamous cell carcinoma (OPC) incidence recently surpassed cervical cancer and is the most common HPV-related cancer in the developed world. HPV16 is in ∼90 % of HPV + OPCs, with episomal genomes in the majority of cases. Most existing HPV16+ cancer cell lines derive from outside the oropharynx and harbor integrated HPV genomes. Thus, there is need for OPC preclinical models to evaluate standard and experimental therapeutics in the presence of episomal HPV16 oncogenic drivers. Here we characterize HPV genome structures in eight HPV16+ OPC patient-derived xenografts (PDXs), and evaluate their responses to standard chemotherapy. HPV genome state was investigated by combining Southern blot, T5 exonuclease assay, whole genome sequencing, and RNAseq data. This analysis revealed complexity and variation in integrated vs. episomal HPV forms across PDXs and demonstrated that four PDXs predominantly contain episomal HPV16. Episomal status did not ensure favorable in vivo responses to cisplatin therapy, despite the more favorable prognosis previously attributed to episomal HPV + tumors; this could be due to the small number present in the dataset. Our analysis establishes PDX models as test platforms for novel therapies designed to target maintenance of the episomal forms of HPV16 that commonly appear in OPC.